2013
DOI: 10.1088/0957-4484/24/50/505708
|View full text |Cite
|
Sign up to set email alerts
|

In situTEM and STEM studies of reversible electromigration in thin palladium–platinum bridges

Abstract: We investigated the reversible electromigration in Pd-Pt nanobridges by means of in situ electron microscopy. Real-time nanometer-scale imaging with scanning transmission electron microscopy was used to determine the material transport. For high current densities (3-5 × 10(7) A cm(-2)), material transport occurs from the cathode towards the anode side, indicating a negative effective charge. The electromigration is dominated by atom diffusion at grain boundaries on the free surface. The reversal of material tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…to reduce the resistance as current increases. A similar effect has been reported for Au and Pd-Pt nanowires 25 . As shown in the inset of Figure 2f corresponding to the SEM image after anti-EM, the void has been refilled with material, naturally explaining the observed decrease in resistance.…”
Section: Electromigration Of Al Nanoconstrictionssupporting
confidence: 86%
See 1 more Smart Citation
“…to reduce the resistance as current increases. A similar effect has been reported for Au and Pd-Pt nanowires 25 . As shown in the inset of Figure 2f corresponding to the SEM image after anti-EM, the void has been refilled with material, naturally explaining the observed decrease in resistance.…”
Section: Electromigration Of Al Nanoconstrictionssupporting
confidence: 86%
“…Indeed, it has been shown that nanogaps, once created, can be closed by using voltage spikes 16,22 while refilling of previously generated voids has been demonstrated in metals such as Al and Pd-Pt [23][24][25] by simply reversing the polarity of the dc current.…”
Section: Introductionmentioning
confidence: 99%
“…Kozlova et al [3] that electromigration in Pt-Pd nanobridges displaces material from the cathode side towards the anode side of the bridge. Consequently this results in an inhomogeneity of the bridge thickness after the electromigration process has ended.…”
Section: Resultsmentioning
confidence: 99%
“…Elsewhere we reported the possibility to follow the electromigration process in Pt [2] and in PtPd nanobridges [3] using in situ transmission electron microscopy (TEM) in bright-field TEM (BF-TEM) and scanning TEM (STEM) modes. In BF-TEM imaging of polycrystalline thin films, there are usually two competing types of contrast: mass-thickness contrast and diffraction contrast, which arises from the difference in orientation of the grains.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies become more important because of the trend to downscale metallic contact lines to nanometer sizes in devices. To our knowledge, the influence of substrate temperature on bridge morphology during electromigration has not yet been reported, only results concerning room temperature (RT) and liquid nitrogen temperature (around 100 K) [2,11,12]. We report here on in situ TEM results of electromigration in Pt nanobridges at substrate temperatures ranging from 100 K to 660 K.…”
Section: Introductionmentioning
confidence: 94%